Targeted Lactic Acid Regulation via Engineered Exosomes for Synergistic Metabolic and Photodynamic Tumor Therapy - Sisi Zhou; Yu Cao; Xianbiao Wang; Songqin Liu (Advanced Healthcare Materials, 2026)
ABSTRACT Tumor cells exhibit a hyper‐glycolytic phenotype, resulting in massive lactic acid (LA) production that acidifies the tumor microenvironment (TME) and fosters immunosuppression. Current lactate‐targeted therapies often lack synergistic dual‐directional regulation. Herein, we engineer an exosomal nanoplatform, PpIX/siRNA@EXO‐LOD, to simultaneously disrupt intra‐ and extracellular LA homeostasis, thereby enabling synergistic metabolic and photodynamic therapy (PDT). The system integrates three key components: protoporphyrin IX (PpIX) for PDT, siRNA targeting monocarboxylate transporter 4 (MCT4) for intracellular metabolic interference, and surface‐displayed lactate oxidase (LOD) for extracellular catalytic starvation. Upon epithelial cell adhesion molecule (EpCAM)‐mediated targeting, the nanovesicle triggers a cascade of synergistic effects. Crucially, siRNA‐mediated silencing of MCT4 induces lethal intracellular acidosis, leading to significant intracellular H 2 O 2 accumulation. This elevated H 2 O 2 level acts as a booster for PpIX‐generated reactive oxygen species (ROS) upon laser irradiation, creating an amplified oxidative stress burst that overwhelms tumor cell defenses. Concurrently, surface‐anchored LOD consumes extracellular LA, alleviates lactate‐induced immunosuppression. In vivo studies demonstrate that this dual‐regulation strategy effectively inhibits tumor growth, downregulates metastasis‐related factors (amphiregulin (AREG), ATP‐binding cassette sub‐family B member 1 (ABCB1)), and reprograms the TME from an immunosuppressive state to an immunologically active state. This work presents a precision nanomedicine strategy that leverages the interplay between metabolic modulation and photodynamic amplification for enhanced cancer treatment.